Odpowiedzi

2009-11-09T17:58:06+01:00
(x+1)²-(y-2)=x²+2(y-1)
x²+1-y-2=x²+2y-1
-3y=1+2
y=1/3

3(x-2)+y²=(y+1)(y-1)
3x-6+y²=y²-y+y-1=
3x=-1+6
3x=5/:3
x=5/3

2x-1/5+3y+2/4=2
2x+3y=2 1/5-2/4
2x+3y=1 24/20-10/20
2x+3y=1 1/5

3x+1/5-3y+2/4=0
3x-3y=-1/5-2/4=
3x-3y=-4/20-10/20
3x-3y=-7/10
2009-11-09T18:10:11+01:00
(x+1)²-(y-2)=x²+2(y-1)
x²+1-y-2=x²+2y-1
-3y=1+2
y=1/3

3(x-2)+y²=(y+1)(y-1)
3x-6+y²=y²-y+y-1=
3x=-1+6
3x=5/:3
x=5/3

2x-1/5+3y+2/4=2
2x+3y=2 1/5-2/4
2x+3y=1 24/20-10/20
2x+3y=1 1/5

3x+1/5-3y+2/4=0
3x-3y=-1/5-2/4=
3x-3y=-4/20-10/20
3x-3y=-7/10